A COMPARATIVE BIOAVAILABILITY OF FUROSEMIDE IN SOLID DISPERSIONS FORMS - Yandi Syukri; Lukman Hakim; Tedjo Yuwono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2001)
Furosemide is a poorly soluble diuretic drug, the solubility of which can be enhanced by solid dispersion with polyvinylpirolidon (PVP). The solid dispersion system was prepared by a solvent method in various ratios of 1 : 5 and 1 : 7 of the drug and PVP, respectively, in order to improve furosemide bioavailability. The bioavailability of furosemide - PVP solid dispersion was compared with pure furosemide (control) and Lasix (reference). The study was done in a cross over design with a single-dose peroral that administered to the white male rabbits (n = 6). Furosemide blood levels were determined spectrofluorometrically by an extraction method. The area under the blood concentration-time curve AUC0 - , peak blood concentration Cmax and time to reach peak blood concentration Tmax were used to compare their bioavailabilities. The solid dispersion systems produced a higher extent of bioavailability than pure furosemide (P < 0,05). On the contrary, no statistically significant difference about the extent of bioavailability between solid dispersion and Lasix (P > 0,05). Finally, furosemide – PVP solid dispersion (1 : 7) was the best formulation with the highest extent of bioavailability and bioequivalence with the Lasix formula.Key Word : Solid dispersion, solubility, dissolution, bioavailability, furosemide.